DIFFERENTIAL DIAMETER SIZE OF PVC TRAP TO CATCH FISH ON PUBLIC WATER IN BUNGARAYA VILLAGE SIAK DISTRICT RIAU PROVINCE - Arifin, Surya; Brown, Arthur; ', Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted on 06 January 2015 in public waterBungaraya village Siak district Riau province. The aim of this research was toinfluence of diameter size of PVC trap on catches. While method of this researchis experimental method. The diameter size of trap : T1 (4 cm), T2 (8 cm) and T3(12 cm). The base on statistical calculation indicated that no significantly effect ofdiameter size of trap on catches. The best result was achieved by T3, T2 and T1with 1,47 kg of 12 fishes, 1,49 kg of 11 fishes and 0,41 kg of 10 fishesrespectively.Keyword : PVC Trap, Public Water